Dr. Georg Huemer — Deep Plane Facelift — Vienna - Huemer, Georg (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Georg Huemer, practicing in Vienna, Austria. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003310; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; austria; vienna